Temporal Patterns in the Abundance and Diet of Acetes erythraeus Nobili 1905 (Crustacea, Decapoda, Sergestidae) in the Nearshore Waters of Iligan Bay, Northern Mindanao, Philippines - Ephrime B. Metillo (Science Diliman, 2002)
Two adjacent nearshore estuaries in Iligan Bay (8°N, 124°E), Northern Mindanao were sampled to investigate annual temporal patterns in the abundance and stomach contents of Acetes erythraeus, and selected hydrometeorological factors. Principal Components Analysis (PCA) reveals temporal variations in A. erythraeus abundance and diet composition that appear to conform not only to the typical northeast and southwest monsoons, but also to three-month seasons (March-April-May [dry hot], June-July-August [wet hot], September-October-November [wet cold], December-January-February [dry cold]). Rainfall and tide largely explain variations of abundance and stomach contents. Peaks in A. erythraeus abundance are similar to those found in other tropical Acetes species whose bimodal temporal distribution patterns coincide with the start of the southwest monsoon and the end of the northeast monsoon. A. erythraeus is a zooplanktivorous omnivore with copepods, ostracods, other crustaceans, and molluscan veligers as the predominant food. A total of twelve (12) diet categories were recorded, including, for the first time, dinoflagellates and tintinnids. A comparison of stomach contents of shrimps, caught before and after midnight, showed higher ingestion after midnight. Diet composition of juvenile and adult shrimps, generally, is independent of sex and sampling location. Although there is overlap in the diet between adults and juveniles, the latter ingest more small-sized food categories.